2004
DOI: 10.1159/000081758
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in Patients with Obstructive Sleep Apnea Syndrome: Course and Physiological Relevance

Abstract: Background: Adiponectin is an adipocyte-derived hormone with anti-inflammatory and insulin-sensitizing properties. Insulin resistance is a typical feature of the obstructive sleep apnea syndrome (OSAS). Objectives: Since nasal continuous positive airway pressure (nCPAP) treatment improves insulin sensitivity in patients with OSAS, we investigated serum adiponectin levels before and during nCPAP treatment to clarify possible interactions between the adiponectin levels and insulin sensitivity in patients with OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 37 publications
9
30
2
2
Order By: Relevance
“…Notably, decreased adiponectin levels in OSAHS were attributed to obesity [197]. In line with the data reporting on unchanged adiponectin levels in OSAHS, longterm nCPAP treatment was also shown to be ineffective [200,201]. As noted earlier, adiponectin is primarily released by adipose tissue and decreases in the obese and yet is affected by oxidative stress.…”
Section: Adiponectinsupporting
confidence: 74%
“…Notably, decreased adiponectin levels in OSAHS were attributed to obesity [197]. In line with the data reporting on unchanged adiponectin levels in OSAHS, longterm nCPAP treatment was also shown to be ineffective [200,201]. As noted earlier, adiponectin is primarily released by adipose tissue and decreases in the obese and yet is affected by oxidative stress.…”
Section: Adiponectinsupporting
confidence: 74%
“…The effects of CPAP treatment may be related to improvement of sleep quality, metabolism, and other factors; therefore, improvement of the drop in adiponectin levels with one-night nCPAP may be due not only to removing hypoxia partly but also to alteration of other OSAHS-related factors. Although we did not investigate the long-term effect of nCPAP treatment in the present study, several reports found no significant changes in serum levels of adiponectin after 3 mo of long-term nCPAP treatment (6,42), suggesting that the lack of a long-lasting change in adiponectin can be explained by the influence of body mass on adiponectin secretion, which was unchanged during nCPAP treatment. Considered together, the results of one-night nCPAP seem different from those of long-term nCPAP treatment.…”
Section: Discussioncontrasting
confidence: 59%
“…In a recent Japanese study [62], plasma adiponectin levels were not different between mild, moderate and severe OSAS patient groups. The plasma adiponectin levels were correlated with the insulin sensitivity of these patients, as calculated using the Homeostasis Model Assessment, which confirms the results of the present author's study [59]. However, although plasma adiponectin was an independent determinant of insulin sensitivity in OSAS patients, plasma adiponectin was more closely related to obesity than to sleep apnoea.…”
Section: The Role Of Adiponectin In Osassupporting
confidence: 89%
“…In a study by the present author [59] of 30 patients with OSAS, it was possible to demonstrate a small decrease in adiponectin serum levels that returned to baseline levels after 3 months of treatment. In these patients, the insulin sensitivity had significantly improved 2 days and 3 months after the onset of nasal CPAP therapy.…”
Section: The Role Of Adiponectin In Osasmentioning
confidence: 65%